Two-Round Treatment With Propidium Monoazide Completely Inhibits the Detection of Dead Campylobacter spp. Cells by Quantitative PCR - Okada, Ayaka; Tsuchida, Mizuki; Rahman, Md. Matiur; Inoshima, Yasuo (Frontiers in Microbiology, 2022)
Campylobacter spp. are known as important food-borne gastroenteric pathogens worldwide. Campylobacter spp. can exist in a viable but non-culturable (VBNC) state under unsuitable environmental conditions, which is undetectable by conventional culture methods. Quantitative polymerase chain reaction (qPCR) can be used to detect VBNC Campylobacter spp.; however, both viable and dead bacteria are detected during qPCR and are indistinguishable. Propidium monoazide (PMA), which can only enter dead bacterial cells through a damaged cell wall/cell membrane, binds to DNA and inhibits qPCR. PMA treatment has been performed along with qPCR (PMA-qPCR) to detect viable bacteria. However, the efficacy of detection inhibition differed among studies, and PMA can potentially enter living cells after changes in cell membrane permeability. In this study, we optimized the PMA treatment method by conducting it before qPCR. Two-round PMA treatment completely inhibited the qPCR signals from dead cells, whereas single-round PMA treatment failed to facilitate this. An optimized PMA-qPCR method was developed using commercial chicken meat, and VBNC Campylobacter spp., which are undetectable using conventional culture-based methods, were successfully detected. In conclusion, this study presents a novel, efficient PMA treatment method for the detection of viable Campylobacter spp., including VBNC Campylobacter spp., in chicken meat. We believe that this method will aid the reliable risk assessment of commercial chicken meat.